Th17, synchronically increased with Tregs and Bregs, promoted by tumour cells via cell-contact in primary hepatic carcinoma. (26th January 2018) - Wang, W; Wang, Z; Qin, Y; Tang, G; Cai, G; Liu, Y; Zhang, J; Zhang, P; Shen, Q; Shen, L; Yu, W
Summary: Documented reports about T helper type 17 (Th17) cells have revealed that Th17 plays a critical role in inflammation and autoimmunity diseases. However, the role of Th17 in cancer remains contradictory. The interplay between Th17 and tumour cells in the tumour microenvironment of primary hepatic carcinoma (PHC) needs to be explored further and the relationship between Th17, regulatory T cells (Tregs ) and regulatory B cells (Bregs ) has not been defined completely. In this study, numerous experiments were undertaken to elucidate the interaction of Th17 and Treg /Breg cells involved in PHC. Our work demonstrated that an increased Th17 was detected in the peripheral circulation and in tumour tissues in PHC patients. In addition, increases in peripheral blood Th17 corresponded with tumour–node–metastasis (TNM) stage progression. Also, further studies indicated that Th17 cells were promoted by tumour cells in the PHC tumour microenvironment through both contact-dependent and -independent mechanisms, but cell-contact played the major important role in promoting the production and proliferation of Th17. When isolated CD4 + CD25 + CD127 low Tregs and CD4 + CD25 – CD127 + non-Tregs were cultured with autologous tumour cells, it implied that the phenotype of Th17 and Tregs was modified by tumour cells in the tumour microenvironment. As well as this, Th17 cells were also found to correlate positively with CD4 + forkhead box protein 3 + Tregs and CD19 + CD5 + CD1d hi Bregs in PHC. Notably, Th17 increased synchronically with Tregs and Bregs in PHC. These findings may provide new clues to reveal the mechanisms of immune escape in PHC. Graphical Abstract: